Penggunaan Minyak Alami dengan Minimum Quantity Lubrication terhadap Hasil Proses Bubut AA 6061 - Setyarini, Putu Hadi; Anam, Khairul; Wahyudi, Muhammad (Jurnal Rekayasa Mesin, 2021)
Environmentally friendly lubricants are lubricants that are easily dissolved in the environment and are not harmful to the ecosystem. It uses to reduce the heat in the contact area so that the machinability of the workpiece and the ability of the chisel will increase. To minimize the use of bio-cutting fluids, lubrication is carried out by minimum drop lubrication in the lathe process. The purpose of this research is to comply with the surface roughness of the workpiece and the shape of the chip. The material used is aluminum 6061, the natural oil used are rubber seed oil, virgin coconut oil, sunflower seed oil, and castor oil. The turning parameters were the depth of cut 0.5 mm, spindle speed of 330 rpm, feed rate 0.231 mm/rev, tool angle 90o, drop lubrication 192 ml/hour, infeed length 100 mm. The results of the research showed that virgin coconut oil has the lowest surface roughness. This is because the viscosity value of virgin coconut oil is very small so that the flow rate is able to work perfectly to lubricate the contact area. It has a thin chip configuration, the tool also wears but did not experience cracks.